Thermal and statistical analysis of the high-Z tungsten-based UFOs observed during the first deuterium high fluence campaign of the WEST tokamak - J. Gaspar; Y. Anquetin; Y. Corre; X. Courtois; M. Diez; A. Ekedahl; N. Fedorczak; A. Gallo; J-L. Gardarein; J. Gerardin; J. Gunn; A. Grosjean; et al. (Nuclear Materials and Energy)
This paper summarizes the observations on the Unidentified Flying Object (UFO) observed during the first high fluence campaign performed in WEST. The campaign was characterized by high erosion and deposition rates, generating dusts and deposits prone to flaking during plasma operation. A total of 686 UFOs have been detected for 384 discharges executed, in which 133 UFOs lead to a disruption. These UFOs appear mostly during the low hybrid heating ramp-up early in the discharges. The mechanisms leading to a disruption is described as well as the delay available to react after the UFO entering in the plasma. The UFOs originate mostly from the high field side corresponding to the thick deposit area. These UFOs can be debris from a preceding disruption (≈27 %) or come from progressive loss of adherence of the thick deposits (≈55 %) under plasma cycling or more likely by disruption on this area. Finally, the thermal resistance of the poorly attached deposits has been calculated in the range from 2.10−4 °C m2/W to 1.10−3 °C m2/W coherent with previous observations in the high field side of the JET divertor.